Respon Pertumbuhan Dan Produksi Tanaman Jagung Manis (Zea Mays Saccharata Sturt) terhadap Pemberian Pupuk Kandang Sapi Di Kabupaten Merauke - Lulu Febriani Bapaimu; Irba Djaja; Jefri Sembiring (Yayasan Literasi Sains Indonesia, 2024)
This research aims to analyze the response of cow manure to the growth and production of sweet corn plants. This research was conducted in May-July 2023 in Marga Mulya Village, Semangga District, Merauke Regency. This research used a randomized block design (RAK) consisting of treatments P0 (without fertilizer), P1 (fertilizer dose 20 tons/ha), P2 (fertilizer dose 25 tons/ha), P3 (fertilizer dose 30 tons/ha), and five repetitions to obtain 20 experimental units. The research results for the growth component treatment showed that plant height gave the highest results in treatment P3 (138 cm), leaf length in treatment P0 (121 cm), and leaf width in treatment P2 (8.14 cm). Meanwhile, the highest number of leaves was in the P2 treatment with (8.56 pieces), the longest cob length in the P2 treatment (19.56 cm), the highest number of rows/cobs in the P1 treatment (15.86 rows), the cob/sample weight in the P2 treatment with (204.04 g), the highest total weight/plot was in treatment P2 (1.48 kg). Providing cow manure has little effect on the growth and production of sweet corn plants in Merauke Regency.